Learning Position and Preferred Internet Content as Factors of Problematic Internet Use in Students - A.B. Kholmogorova; E.Yu. Kazarinova; A.A. Rakhmanina (Moscow State University of Psychology and Education, 2022)
The role of preferred content on the Internet and positions in educational activities for problematic Internet use or the Internet addiction among students have been hardly studied. The subject position in educational activity reflects the high motivation and independence of students in mastering educational material. A hypothesis is put forward about the protective role of the subject position as a factor of protection against the Internet addiction or problematic Internet use by students. The sample consisted of 186 school and university students aged 13 to 23 years (M=18,7), 92 male and 94 female. The following techniques were used in the study: "General scale of problematic Internet use-3" (A.A. Gerasimova, A.B. Kholmogorova, 2018), "Questionnaire of preferred Internet content", the questionnaire "Subject position" (Yu.V. Zaretsky, V.K. Zaretsky, I.Y. Kulagina, 2014). The study revealed that a pronounced subject position in educational activities (β=-0,169; p=0,001) and a preference for educational content (β=-0,389; p<0,001) reduce the problematic Internet use. The preference for entertainment and informational content, as well as high frequency of communication and self-presentation on the Internet are associated with objective and negative positions in educational activities and increase the Internet addiction or problematic Internet use in students of schools and universities (R2=0,388, F=22,796). The conclusions of our study are preliminary, it is necessary to expand the sample and further validate research methods.